1993
DOI: 10.1111/j.1574-695x.1993.tb00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni: Specific oligonucleotides and DNA probes for use in polymerase chain reaction-based diagnosis

Abstract: A 1189 base-pair long DNA fragment, VS1, was isolated from a Campylobacter jejuni CIP 70.2 cosmid library and was found to contain regions specific for this bacterial species. For detection and identification of C. jejuni, two oligonucleotides derived from the VS1 sequence were used as primers in polymerase chain reaction tests on genomic DNAs from 38 campylobacter and from 10 non-Campylobacter strains. A specific, 358 base-pair long DNA fragment was amplified only when C. jejuni DNA was used as a target. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Examples of the former type have been described for identifying several enteric campylobacteria, including C. jejuni subsp. jejuni (87,137,166,170), C. coli (170), C. hyointestinalis (60,61), C. mucosalis (60), C. helveticus (162), H. canis (165), and Lawsonia intracellularis (59,103). A number of randomly generated, species-specific probes for identifying H. pylori have also been developed (32,93,178,196), some of which (32,93,178) may also be used for epidemiological typing of this organism in Southern hybridization assays.…”
Section: Nucleic Acid Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of the former type have been described for identifying several enteric campylobacteria, including C. jejuni subsp. jejuni (87,137,166,170), C. coli (170), C. hyointestinalis (60,61), C. mucosalis (60), C. helveticus (162), H. canis (165), and Lawsonia intracellularis (59,103). A number of randomly generated, species-specific probes for identifying H. pylori have also been developed (32,93,178,196), some of which (32,93,178) may also be used for epidemiological typing of this organism in Southern hybridization assays.…”
Section: Nucleic Acid Probesmentioning
confidence: 99%
“…However, the positive reaction of the C. jejuni-C. coli probe of Taylor and Hiratsuka (170) with some stool samples found to be culture negative may indicate that probes (when developed to optimal levels) may be valuable tools in demonstrating the limits of cultural methods. The sensitivity of such assays may be improved by using a PCRgenerated template as the target oligonucleotide, an approach which has been used for C. fetus (8), C. jejuni (134,166), H. hepaticus (5), and H. pylori (42,75,178). In such assays, the disadvantages of PCR must also be considered (172; also see below).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Identification to the species level was achieved by phenotypic methods [8] based on biochemical and physiological characteristics (i.e., growth at 25°C, catalase activity and hippurate hydrolysis test) and susceptibility to antibiotics (nalidixic acid and cephalothin). The first 100 isolates were also examined with a PCR species identification assay for C. jejuni and C. coli [9,10]. Sequencing of the 16S rRNA gene was used to analyse discordant results (see below).…”
Section: Bacteriamentioning
confidence: 99%
“…jejuni and C. fetus real‐time PCRs and the phenotypic methods used as a standard. Analysis by standard PCR [9,10] and 16S rDNA sequencing demonstrated that two of the discrepant isolates were hippurate‐negative C. jejuni strains, resulting in an erroneous phenotypic identification, while the third was an isolate of C. coli that contained a gyrA gene typical of C. jejuni , resulting in misidentification by the FRET assay. This last discrepant result could possibly be explained by horizontal transfer of the gyrA gene from C. jejuni to C. coli .…”
Section: Identification Of Campylobacter Spp In Clinical Specimensmentioning
confidence: 99%
See 1 more Smart Citation